Roujingo Pada Karakter Faruzan Dari Genshin Impact: Kajian Psikolinguistik - Lula Kaneisya Nabila; Dedi Suryadi (Universitas Diponegoro, 2026)
Language functions not only as a means of communication but also as a marker of identity that shapes how individuals perceive themselves and are perceived by others. From a psycholinguistic perspective, language reflects mental processes, identity construction, and social interaction. In fictional media, character identity is often constructed through stereotypical language styles, such as yakuwarigo, including roujingo, which is typically associated with elderly characters. However, this style may also be used by younger-looking characters, such as Faruzan in Genshin Impact. This study aims to examine the psycholinguistic function of roujingo in constructing and negotiating senior identity, particularly in cases where linguistic expression does not align with visual appearance. Using a descriptive qualitative approach, the data were collected from Faruzan’s voicelines and selected dialogues involving other characters. The findings show that Faruzan consistently employs roujingo as a top-down linguistic strategy to construct a senior persona. However, this constructed identity is not always perceived uniformly by interlocutors. The mismatch between linguistic and visual cues leads to varied interpretations, ranging from perceived authority to social discomfort. These results indicate that the meaning of roujingo is not fixed, but dynamically negotiated through interaction, highlighting the role of language in mediating identity and perception in fictional discourse.